Desempenho, características das fibras musculares e das carcaças de cordeiros nascidos de ovelhas suplementadas com diferentes níveis de proteína - Santello, Graziela Aparecida (2008)
Material treatment effect and feedlot diets were evaluated on carcasses characteristics, diameter and frequencies of muscle fibers, as well as the correlation with average daily gain (ADG), shearing force and weight losses for cooking. Eighty Santa Inês ewes were observed, with average weight 47.79 ± 3.76 kg, mated with a Dorper ram and supplemented with different levels of crude protein (CP) in the initial third of pregnancy (i20; 22.48; 26.52 and 35.65% of CP). Feedlot diets for lambs were: control = without sunflower grain (16.18% CP and 79.64% TDN); sunflower grain = addiction of sunflower grain (15.03% CP and 78.96% TDN). Biopsy of Semitendinosus muscle of offspring and post-mortem samples of left Semitendinosus and Longissimus lumborum muscles were made in lambs to determine diameter and frequency of muscle fiber type (50, FOG and FG). The male lambs were slaughtered with an average of 32.31 ± 1.75 k of live weight. There was no influence of maternal treatment (P>0.05) on the weight development of the male and female lambs from birth to finishing. The sex influenced (P 0,05) weight of the lambs on the birth (LWB) and at 58 days (LW58). The kind of birth influenced (P<0.05) LWB, LW58 and the dairy average gain 'from the birth to wearing (DAG 0-58). There was no difference in the maternal treatment (P<0.05) in the number (2813.45) and diameter (13.16 um) of the muscle fibers to the offspring. There was effect of the feedlot diet (P<0.05) for diameter in the Longissimus lumborum of the SO (control = 27.05 and sunflower grain 28.7 1 j.tm), and diameter in Semitendinosus I' I'G (control = 33.51 and grain sunflower = 35.51 j.tm). Correlation was verified ( 0,05) among ADG with the three types of fibers (0.42; 0.46 and 0.39) in the lungissimus lumborum. The carcasses of the lambs presented differences (P<0.05) for conformation (3.00 and 3.32), fat color (1.90 and 1.60) and meat color (1.50 and 1.64), respectively for finishing diet controls or sunflower grain. The type of birth influenced (P<0.05) area of loin eye (simple = 12.37 and double = 11.26 em2) and the measure A (Miinple = 56.15 and double = 52.60 mm). There was no correlation of the diameter and frequency of the types of skeletal muscle fibers with the shearing forces and weight tosses in cooking. There was a decreasing linear regression for maternal treatment (P),05) in the weight in the origin, slaughter weight, hot carcass weight, cold carcass weight and carcass compactness index. There was effect of the feedlot diet and type of birth (P<0.05) for weight in the origin (control = 32.60 and sunflower grain = 32.09 kg; simple = 32.84 and double = 3 1.18 kg), slaughter weight (control 30.56 and sunflower = 29.60 kg; simple = 30.73 and double = 29.09 kg) and carcass compactness index (LC)controls 0.22 and sunflower grain = 0.21 kg/cm; simple = 0.22 and double = 0.21 iq/em). The mean yield value found were 34.12% for leg; loin of 10.71%; palette of i85i%; rib of 8.26%; discovered rib of 10.40%; low of 10.90% and neck of 7.07%. The feedlot diet did not influence the muscle percentage (6 1.62%), fat (20.86%) and hone (17.52%) in the loin. The extra carcass components did not present difference among treatment control and sunflower grain. The diameter and number of the skeletal muscle fibers of lambs were not influenced by maternal treatment. The supplement with 15.20% of CP was the one that presented the highest birth weight of lambs. So it is possible to use the smallest CP level for not having difference in the diameter and number of the muscular fibers. The lambs can be finished with diets containing or not sunflower grains.